Navigating Belonging and Identity: Representation of Indonesian Muslims in the United Kingdom - Rizal, Efri Arsyad (Islamic Studies Review, 2025)
Indonesian Muslims, despite navigating their adaptations to new life circumstances in the United Kingdom, actively contribute to the country's socio-cultural landscape through academia, festivals, art exhibitions, and culinary events that promote and preserve Indonesia’s cultural heritage. Examining Indonesian Muslim organizations in the UK such as KIBAR, PCINU UK, PCIM Britania & Irlandia, and Indonesia Islamic Centre (IIC) London, this research explores the sense of belonging and unbelonging among Indonesian Muslims in the UK, focusing on individual and collective identities. By employing Christensen's framework on belonging and unbelonging and Mossovici’s framework of social representation, this study discusses how Indonesian Muslims construct and uphold their identity in different circumstances. The results reveal that Indonesian Muslims navigate their identity by preserving their traditions and practically applying their traditions in a diaspora setting through religious agendas. This research also highlights their religious commitment and contribution to socio-cultural problems in their homeland, Indonesia.